Storage period and temperature as determinants of egg quality: An analytical study: Storage effects on egg quality - SONALE, NAGESH; Rokade, Jaydip; Kumar, Akilesh; M, Monika; Abhijeet, Champati; Wadajkar, Prasad; Tiwari, Ashok Kumar (Indian Journal of Poultry Science, 2025)
The study aimed to evaluate the impact of cold and room-temperature storage on the external and internal quality of eggs, as well as their microbial quality. A total of 108 fresh white eggs from the ICAR-CARI layer house were divided into two groups: the T1 group, stored at room temperature, and the T2 group, stored at 4°C. Egg quality was assessed on days 0, 3, 6, 12, 18, and 24. Results showed that egg quality decreased more significantly (p < 0.05) in the T1 group, with reductions in measurements like egg pH, and albumen quality. In contrast, eggs stored in cold conditions maintained a more stable quality across all parameters (p < 0.05). Microbial analysis indicated that eggs stored at room temperature had an increasing bacterial count, starting from 3.64 cfu/ml on day 0 and reaching 6.50 cfu/ml by day 24. However, eggs stored in cold conditions exhibited much lower bacterial growth, with a total plate count (TPC) of 3.64 cfu/ml on day 0, only rising slightly to 4.33 cfu/ml by day 24.